Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00268-015-3165-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Carotid Endarterectomy in Symptomatic and Asymptomatic Patients with Ipsilateral Intracranial Stenosis

Abstract: This study has shown that patients with and without CTL who underwent CEA had a similar occurrence of perioperative adverse events (probably due to the extremely low incidence of perioperative complications) and comparable late outcomes, suggesting that the presence of CTL does not justify refusing CEA for patients who could benefit from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
2
1
0
Order By: Relevance
“…Our results were similar to that of few other studies in Asian countries, where the predominant presentation was with a stroke [12–14, 19]. This is in contrast to the Western world wherein more than 50% of patients undergo CEA after a hemispheric or a retinal TIA [811].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results were similar to that of few other studies in Asian countries, where the predominant presentation was with a stroke [12–14, 19]. This is in contrast to the Western world wherein more than 50% of patients undergo CEA after a hemispheric or a retinal TIA [811].…”
Section: Discussionsupporting
confidence: 89%
“…An analysis from the NASCET cohort reported that the benefit of CEA was less certain in those with severe intracranial atherosclerosis in view of smaller numbers [22]. Our results were similar to a large single-center Italian study that reported no difference in the occurrence of perioperative events among those with and without coexistent tandem intracranial atherosclerosis, who underwent CEA [11]. The presence of a proximal lesion may overestimate a distal lesion due to reduced flow.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The previous study showed that patients with intracranial lesions benefit less from endarterectomy during oneyear follow-up period [13]. Other study demonstrated that patients with and without carotid tandem lesion who underwent CEA had similar rates of stroke and death [14][15]. Ballotta et al [14] analyzed 1,143 patients who underwent CEA.…”
Section: Discussionmentioning
confidence: 99%
“…Other study demonstrated that patients with and without carotid tandem lesion who underwent CEA had similar rates of stroke and death [14][15]. Ballotta et al [14] analyzed 1,143 patients who underwent CEA. Their results showed no significant perioperative ipsilateral strokes difference between those patients with (0.9 %) and without (0.5 %) carotid tandem lesion (P = 0.62).…”
Section: Discussionmentioning
confidence: 99%